Rational exuberance: The fundamentals of pricing firms, from blue chip to "dot com" - Mark Kamstra (Federal Reserve Bank of Atlanta, 2001)
The author establishes that classic firm-valuation methods based on dividends (or equivalently free cash flows or residual income) can be modified to be based on any financial variable (V), such as sales, given V is cointegrated with the fundamental value (P) of the firm. The variable V (or a fraction of V) replaces dividends in the valuation formula, through a share liquidation scheme tied to V/P. The author shows that this modified valuation formula is equivalent to the classic fundamental valuation formula based on dividends, provided the share liquidation implicit in this scheme is accounted for. The use of nondividend information V permits an estimate of the fundamental value of a firm which should be more reliable than an estimate based on dividends alone, as dividends are well-known to be smoothed and can provide a poor indicator of future cash payments to investors. This approach is shown to complement existing valuation approaches that use dividends, permitting the fundamental valuation of firms which may or may not pay out dividends, have negative earnings, negative free cash flows, or even a negative book value (of shareholder equity). This extension of the classic fundamental valuation formula also provides a new methodology for calculating the fundamental asset price of any firm, including "dot-com" firms and privately held firms, utilizing nondividend information, such as sales, explicitly. Using dividends augmented with a cash flow from share liquidation, the author restates popular valuation methods, including the Gordon growth model, the residual income model, and the free cash flow model.
Keywords: 330; Asset pricing